Preparation method of explosion-proof thickened wear-resistant rubber and plastic pipe

Through the multi-layer rubber and plastic pipe preparation method, combined with the ultra-high wear-resistant composite layer, explosion-resistant energy absorption layer and explosion-proof impact barrier layer, the wear and explosion-proof problems of traditional rubber and plastic pipes under complex working conditions is solved, and the wear resistance, explosion-resistant ability and explosion-proof performance of the pipe are significantly improved.

CN119795678AActive Publication Date: 2025-04-11ZHUJI SHENTONG RUBBER & PLASTIC PIPE CO LTD

Patent Information

Application Number
CN202411958273.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-11
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

Traditional rubber and plastic pipes are prone to wear and explosion accidents under complex working conditions, and lack wear resistance and safety, making it difficult to cope with the challenges of various industrial environments.

Method used

The preparation method of multi-layer structure is adopted. The inner layer is an ultra-high wear-resistant composite layer, the middle layer is an explosion-resistant energy absorption layer, and the outer layer is an explosion-proof impact barrier layer. Through the combination of nano-level materials and high-performance fibers, the wear resistance, explosion-resistant ability and explosion-proof performance of the pipe are enhanced.

Benefits of technology

It significantly improves the compressive strength, high temperature resistance and chemical corrosion resistance of rubber and plastic pipes, reduces the risk of explosion and corrosion under complex working conditions, extends the service life of the product and reduces maintenance costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005216439190000052
    Figure BDA0005216439190000052
  • Figure BDA0005216439190000061
    Figure BDA0005216439190000061
  • Figure BDA0005216439190000062
    Figure BDA0005216439190000062
Patent Text Reader

Abstract

A preparation method of an explosion-proof thickened wear-resistant rubber and plastic pipe belongs to the field of rubber and plastic pipes, the explosion-proof thickened wear-resistant rubber and plastic pipe comprises an inner layer, a middle layer and an outer layer, the inner layer is an ultrahigh wear-resistant composite layer, is compounded by polytetrafluoroethylene and polyimide, and is reinforced by nanoscale silicon carbide particles and graphene; the middle layer is an anti-explosion energy absorption layer, a shape memory polymer is combined with crosslinked polyethylene to form an intelligent material capable of responding to pressure change, and a high-strength aramid fiber and carbon fiber composite material is embedded into the middle layer; the outer layer is an anti-explosion impact barrier layer, nano ceramic reinforced silicone rubber is adopted, and ultra-high molecular weight polyethylene is combined with ceramic particles, so that the high pressure resistance and the explosion resistance are improved. The inner layer adopts the high-performance material and the nano reinforced filler, so that the wear resistance is remarkably improved; a self-repairing coating technology is introduced into the outer layer, automatic healing of local damage is achieved through a microcapsule structure, the service life of the product is prolonged, and the maintenance cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of rubber-plastic pipes, and more specifically to a method for preparing an explosion-proof, thickened, and wear-resistant rubber-plastic pipe. Background Art

[0002] In the field of rubber and plastic pipe manufacturing, the wear resistance and safety of traditional products still need to be improved, especially under complex working conditions, where wear and explosion accidents are prone to occur. Rubber and plastic pipes face different challenges in different industrial environments. Ordinary rubber and plastic pipes not only limit their scope of use but also increase maintenance costs.

[0003] The patent with publication number CN217597982U discloses a flame-retardant multi-layer thickened explosion-proof rubber-plastic pipe, including a pipe body, a flame-retardant layer is arranged on the outside of the pipe body, a rubber-plastic layer is arranged on the inside of the flame-retardant layer, a reinforcement ring is arranged inside the rubber-plastic layer, a polyester braided layer is arranged on the inner side wall of the rubber-plastic layer, a modified PVC layer is arranged on the inner side wall of the polyester braided layer, a reinforcement rib is arranged on the inner side wall of the modified PVC layer, and an aluminum foil sheath is arranged on the outer side wall of the reinforcement ring. The flame-retardant layer provided in the utility model improves the flame-retardant effect of the rubber-plastic pipe when in use, so that the pipe can be flame-retardant when encountering a fire, and the pipe is prevented from being damaged by the fire. Although the scheme is designed with a multi-layer structure, the thickness is enhanced, the explosion-proof ability is enhanced, and it has a flame-retardant effect, but the wear resistance and corrosion resistance are not strong, and it still cannot cope with a variety of complex industrial environments. Summary of the invention

[0004] To address this problem, this proposal proposes a method for preparing explosion-proof, thickened, and wear-resistant rubber-plastic pipes.

[0005] An explosion-proof, thickened, wear-resistant rubber-plastic pipe, comprising an inner layer, an intermediate layer, and an outer layer, wherein the inner layer is an ultra-high wear-resistant composite layer, which is a composite of polytetrafluoroethylene and polyimide, and has extremely high wear resistance and thermal stability, and is reinforced with nano-scale silicon carbide particles and graphene to further improve wear resistance and high temperature resistance; The middle layer is an explosion-proof energy absorption layer, which uses shape memory polymers combined with cross-linked polyethylene to form an intelligent material that can respond to pressure changes, and is embedded with high-strength aramid fibers and carbon fiber composite materials to further enhance tensile strength and explosion resistance; The outer layer is an explosion-proof impact barrier layer, which uses nano-ceramic reinforced silicone rubber to improve the material's impact resistance and high pressure resistance. Ultra-high molecular weight polyethylene is combined with ceramic particles to improve high pressure resistance and explosion resistance, while ensuring that the outer layer has a certain degree of flexibility; The method for preparing the explosion-proof, thickened and wear-resistant rubber-plastic pipe comprises the following steps: S1. The raw materials are fully dried before feeding, wherein the drying temperature of polytetrafluoroethylene is 120°C and the drying time is 6 hours; the drying temperature of polyimide is 160°C and the drying time is 4 hours; the drying temperature of ultra-high molecular weight polyethylene is 70°C and the drying time is 3 hours; S2. Each layer of material is preheated in sections before entering the extruder head: the first section preheating temperature is 50-100℃ to improve the initial flexibility of the substrate, the second section preheating temperature is 100-150℃ to soften the polymer material, and the third section preheating temperature is the material melting temperature + 10-20℃ to ensure optimal fluidity; the insulation time of each heating area is 1-3 minutes; S3, adopt multi-head co-extrusion system, each head controls a layer of material, the barrel temperature is set to 250-320℃ for the inner layer, 220-270℃ for the middle layer, and 180-230℃ for the outer layer, and the screw speed is maintained at 60-90 rpm to ensure uniform melting of the material; S4. Through a multi-head co-extrusion die, the molten multi-layer materials are gradually compounded, and the flow channel design in the mold is used to achieve uniform superposition of multiple layers. The mold pressure is controlled at 10-20MPa to prevent bubble generation, and then the temperature is gradually reduced through a water cooling system with a cooling rate of 1-3℃ / second to ensure the stability of the pipe size.

[0006] Preferably, polyurethane is also introduced into the inner layer as a flexible and self-lubricating layer to reduce the friction coefficient and improve the smoothness of fluid transportation in the tube. An ultra-high wear-resistant composite material (PTFE+PI+SiC+graphene) is used to make the inner surface of the tube have excellent wear resistance and corrosion resistance.

[0007] Preferably, the middle layer also adds pressure-sensitive phase change material, which can absorb energy and diffuse pressure under the action of explosion shock wave to avoid pipe rupture. The explosion resistance of the pipe is enhanced by shape memory polymer (SMP) and aramid carbon fiber network. When impacted, the layers will automatically absorb shock wave energy to reduce the peak pressure of the explosion shock wave.

[0008] Preferably, the outer side of the outer layer is coated with a flame retardant coating containing fluoride to effectively resist high temperature and flame propagation, and a composite structure of ceramic reinforced silicone rubber and ultra-high molecular weight polyethylene (UHMWPE) is adopted to ensure that the pipe has excellent impact resistance and pressure resistance, and the outside can effectively resist the transmission of explosion or shock wave.

[0009] Preferably, the explosion-proof, thickened, and wear-resistant rubber-plastic pipe interface adopts a double sealing structure to ensure the sealing of gas and liquid and avoid leakage of high-pressure media.

[0010] The explosion-proof, thickened, and wear-resistant rubber-plastic pipe joint part adopts a metal + rubber composite design to enhance the pressure bearing capacity and avoid rupture caused by excessive pressure at the joint.

[0011] Preferably, after S4, there are further steps: S5. A layer of self-repairing functional coating is applied on the outer layer of the pipe by spraying, and a thin film with self-repairing ability is formed on the surface of the pipe using self-healing resin encapsulated in microcapsules.

[0012] Preferably, the shell material of the microcapsule is polyurethane, and the core is epoxy resin; the liquid epoxy resin is dispersed in the water phase by interfacial polymerization, and the capsule shell is formed by cross-linking reaction, wherein the dispersion temperature is 30-50°C, the dispersion time is 2-4 hours, the stirring speed is 2000-3000rpm, and the capsule size is controlled in the range of 10-100μm; Then, 40–60wt% polyurethane resin is selected as the base material, 20–30wt% microcapsule content is added to the solvent dimethylformamide, the coating viscosity is adjusted to 500–800cps, and the coating is applied to the outer layer of the pipe by spraying, where the coating thickness is 50–200μm, the temperature is 100–120℃, and the heating time is 30–60 minutes. After the coating is cured, a dense self-healing film is formed. When microcracks appear, the microcapsules rupture and release the repair fluid to quickly seal the cracks.

[0013] Preferably, after S5, there is further the following step: S6, introducing functional ions high-energy nitrogen ions and ammonium chloride ions into the deep layer of the pipe by ion bombardment to enhance oxidation resistance, chemical corrosion resistance and adhesion strength.

[0014] Preferably, the S6 comprises the following steps: S6.1. Use high-energy ion implantation equipment, equipped with two ion sources, nitrogen ion and ammonium chloride ion, to ensure that the purity of the ion source is ≥ 99.99%, and maintain the pressure in the chamber at 10 -4 –10 -6 Pa, to avoid oxygen or moisture interfering with the ion implantation effect.

[0015] S6.2. Ultrasonic cleaning of the pipe using ethanol to remove surface oil, dust and other contaminants for 10–15 minutes; S6.3. Use argon gas to clean the surface, activate the molecules on the surface of the tube, and improve the ion attachment effect. The argon gas flow rate is 20-50 standard cubic centimeters per minute, the time is 5-10 minutes, and the power is 100-200W.

[0016] S6.4. Fix the tube on the rotating sample stage to ensure that the ion beam evenly bombards every part of the tube. The sample stage rotates at a speed of 10-30rpm to ensure uniform ion coverage. The injection angle is 45°-90° to improve the ion penetration depth and uniformity. Bombardment time per unit area: 10-30 seconds. Penetration depth: control the ion penetration depth to 1-5μm S6.5. After the injection is completed, anneal the tube in a nitrogen environment to release the thermal stress generated during the ion injection process.

[0017] Compared with the prior art, the advantages of the present invention are: (1) The present invention greatly improves the compressive strength, high temperature resistance and chemical corrosion resistance of the rubber-plastic pipe through deep injection of functional ions and material structure design, and significantly reduces the risk of explosion and corrosion under complex working conditions.

[0018] (2) The inner layer of the present invention adopts high-performance materials and nano-reinforced fillers to significantly improve wear resistance; the outer layer introduces self-healing coating technology to achieve automatic healing of local damage through the microcapsule structure, thereby extending the product service life and reducing maintenance costs.

[0019] (3) The innovative preparation process of the present invention ensures the stability of production efficiency and product quality, while adapting to the needs of various industrial environments, reducing the equipment maintenance frequency and subsequent maintenance costs of corporate customers, and improving market competitiveness. DETAILED DESCRIPTION

[0020] The present application is further described in detail below in conjunction with examples, comparative examples and performance testing experiments. These examples should not be construed as limiting the scope of protection claimed in the present application.

[0021] Examples 1-7 Embodiment 1: An explosion-proof, thickened, wear-resistant rubber-plastic pipe comprises an inner layer, an intermediate layer, and an outer layer, wherein the inner layer is an ultra-high wear-resistant composite layer, which is a composite of polytetrafluoroethylene and polyimide, and is reinforced with nano-scale silicon carbide particles and graphene; The middle layer is an explosion-proof energy-absorbing layer, which uses shape memory polymers combined with cross-linked polyethylene to form an intelligent material that can respond to pressure changes and is embedded with high-strength aramid fibers and carbon fiber composites; The outer layer is an explosion-proof impact barrier layer, which uses nano-ceramic reinforced silicone rubber and combines ultra-high molecular weight polyethylene with ceramic particles to improve high pressure resistance and explosion resistance; A method for preparing an explosion-proof, thickened, and wear-resistant rubber-plastic pipe comprises the following steps: S1. The raw materials are fully dried before feeding, wherein the drying temperature of polytetrafluoroethylene is 120°C and the drying time is 6 hours; the drying temperature of polyimide is 160°C and the drying time is 4 hours; the drying temperature of ultra-high molecular weight polyethylene is 70°C and the drying time is 3 hours; S2. Each layer of material is preheated in sections before entering the extruder head. The first preheating temperature is 50-100°C to improve the initial flexibility of the substrate. The second preheating temperature is 100-150°C to soften the polymer material. The third preheating temperature is the melting temperature of the material + 10-20°C. The insulation time of each heating area is 1-3 minutes. S3, using a multi-head co-extrusion system, each head controls a layer of material, the barrel temperature is set to 250-320℃ for the inner layer, 220-270℃ for the middle layer, and 180-230℃ for the outer layer, and the screw speed is maintained at 60-90 rpm; S4, through a multi-head co-extrusion die, the molten multi-layer materials are gradually compounded, and the flow channel design in the mold is used to achieve uniform superposition of multiple layers, wherein the mold pressure is controlled at 10-20MPa to prevent bubble generation, and then the temperature is gradually reduced through a water cooling system, with a cooling rate of 1-3℃ / second; S5. A layer of self-repairing functional coating is applied on the outer layer of the pipe by spraying, and a thin film with self-repairing ability is formed on the surface of the pipe using self-healing resin encapsulated in microcapsules.

[0022] The shell material of the microcapsule is polyurethane, and the core is epoxy resin. The liquid epoxy resin is dispersed in the water phase by interfacial polymerization, and the capsule shell is formed by cross-linking reaction. The dispersion temperature is 30-50°C, the dispersion time is 2-4 hours, the stirring speed is 2000-3000rpm, and the capsule size is controlled in the range of 10-100μm. Then, 40–60wt% polyurethane resin is selected as the base material, 20–30wt% microcapsule content is added to the solvent dimethylformamide, the coating viscosity is adjusted to 500–800cps, and the coating is applied to the outer layer of the pipe by spraying, wherein the coating thickness is 50–200μm, the temperature is 100–120°C, and the heating is performed for 30–60 minutes.

[0023] S6. Through ion bombardment, functional ions high-energy nitrogen ions and ammonium chloride ions are introduced into the deep layer of the pipe to enhance oxidation resistance, chemical corrosion resistance and adhesion strength.

[0024] S6.1. Use high-energy ion implantation equipment, equipped with two ion sources, nitrogen ion and ammonium chloride ion, to ensure that the purity of the ion source is ≥ 99.99%, and maintain the pressure in the chamber at 10 -4 –10 -6 Pa; S6.2. Ultrasonic cleaning of the pipe using ethanol to remove surface oil, dust and other contaminants for 10–15 minutes; S6.3. Use argon gas to clean the surface, activate the molecules on the surface of the tube, and improve the ion attachment effect. The argon gas flow rate is 20-50 standard cubic centimeters per minute, the time is 5-10 minutes, and the power is 100-200W; S6.4. Fix the tube on a rotating sample stage to ensure that the ion beam evenly bombards every part of the tube. The sample stage rotation speed is 10–30 rpm, the injection angle is 45°–90°, the bombardment time per unit area is 10–30 seconds, and the ion penetration depth is controlled at 1–5 μm. S6.5. After the injection is completed, the tube is annealed in a nitrogen environment to release the thermal stress generated during the ion injection process.

[0025] Embodiment 2: The difference from Embodiment 1 is that the inner layer material is polytetrafluoroethylene; Embodiment 3: The difference from Embodiment 1 is that the inner layer material is polyimide; Embodiment 4: The difference from Embodiment 1 is that the inner layer is not reinforced with nano-scale silicon carbide particles and graphene; Embodiment 5: The difference from Embodiment 1 is that the middle layer does not embed the high-strength aramid fiber and carbon fiber composite material; Embodiment 6: The difference from Embodiment 1 is that the outer layer material is nano-ceramic reinforced silicone rubber; Embodiment 7: The difference from Embodiment 1 is that the outer layer material is ultra-high molecular weight polyethylene; Comparative tests were conducted on Examples 1-7 to test the explosion-proof and wear-resistant capabilities of different rubber-plastic pipes. The test method is as follows: 5 rubber-plastic pipes (35 in total) were made from each example, each with a length of 1 meter. 1. Explosion-proof capability test Step 1: Ensure that both ends of each rubber-plastic tube are sealed, inject dry air, and set the initial pressure to 0.5MPa; Step 2: Fix the pipe in the high-pressure chamber, and the sensor records its pressure bearing data. Gradually increase the pressure at a rate of 0.5MPa / min to 10MPa, and maintain it for 10 minutes to check for leakage, cracks or failure. Step 3: Pressurize to the limit, continue to increase the pressure until the pipe ruptures, and record the rupture pressure and deformation data; Step 4: Explosion-proof energy absorption performance evaluation, calculation of energy absorption efficiency η Energy calculation formula: Where P maxis the bursting pressure, and V is the volume change.

[0026] Step 5: Record the rupture pressure, deformation, and post-rupture morphology (microscopic analysis) of each pipe.

[0027] 2. Wear resistance test Step 1: Cut each pipe to obtain a sample with a length of 10 cm, and polish the surface with sandpaper to ensure the initial surface consistency; Step 2: Measure and record the initial mass of the sample, accurate to 0.001g; Step 3: Test on a DIN wear tester. The test conditions are as follows: pulley speed 200rpm; load force 10N; test time 60 minutes; Step 3: Record the friction surface temperature and thickness loss of the sample during the test; Step 4: After the test, measure the remaining mass of the sample and calculate the wear rate Step 5: Use SEM or AFM to observe the worn area and record the depth, width and material peeling characteristics of the surface damage.

[0028] The test results are shown in Table 1 Table 1 The test results show that Example 1 performs best in terms of burst pressure and energy absorption efficiency, and can be used as the optimal choice for explosion-proof performance.

[0029] Comparative Examples 1-5 Comparative Example 1: The difference from Example 1 is that the shell material of the self-repairing functional coating is polyurea, and the core material is epoxy resin; Comparative Example 2: The difference from Example 1 is that the shell material of the self-repairing functional coating is silicon dioxide, and the core material is graphite suspension; Comparative Example 3: The difference from Example 1 is that there is no step S5; Comparative Example 4: The difference from Example 1 is that the functional ions further include silicon ions; Comparative Example 5: The difference from Example 1 is that there is no step S6; Example 1 was compared with Comparative Examples 1-3 to test the repair speed at different temperatures. The test method is as follows: The standard for defining the completion of repair is that the degree of closure of the injured part is ≥95%, observed under a microscope (magnification ≥100x), and the repair time is counted from the self-healing process after the injury until the repair standard is met.

[0030] Step 1: Prepare test samples according to the coating schemes of Example 1 and Comparative Examples 1-3, ensure that the surface is uniform and meets the thickness standard (50-200 μm), and clean all samples, wipe them with ethanol to remove surface stains, and place them in an environment with a temperature of 25°C and a humidity of 50% RH; Step 2: Use a scratch tester to generate a standardized crack on the coating surface of each sample. The crack depth is 50 μm, the width is 20 μm, and the crack length is 10 mm. Stop the instrument immediately after the crack is generated and mark the start time. Step 3: Place the sample under a microscope, observe the crack repair process, record the time when the crack is closed ≥ 95%, take micrographs every 1 minute, and perform image analysis of the crack closure degree. After the test is completed, record the repair time and save the micrographs for subsequent analysis; Step 4: Place the samples in test chambers simulating high temperature (50° C.) and high humidity (90% RH), and repeat steps 2 and 3.

[0031] The test results are shown in Table 2 Table 2 Example 1 and Comparative Examples 4 and 5 were compared to test the corrosion resistance of rubber-plastic pipes under different environments. The test method is as follows: Step 1: Prepare samples of Example 1, Comparative Example 4 (containing silicon ions) and Comparative Example 5 (without ion implantation treatment), ensure that the sizes are consistent, clean the sample surfaces, rinse with deionized water and then dry; Step 2: Soak the samples in 3.5% NaCl, 10% H2SO4 and 10% NaOH solutions respectively, keep them completely immersed, take out the samples every 24 hours, rinse them with deionized water and dry them, weigh and record the mass loss, continue soaking for 72 hours, and record the total mass loss; Step 3: In a salt spray test chamber, spray 5% NaCl solution at a spray rate of 1-2 mL / h for 72 hours, take samples every 24 hours, observe and record surface changes; Step 4: After the corrosion test is completed, the tensile strength of the sample is tested to compare the change in tensile strength before and after corrosion. The tensile strength retention rate is recorded using a tensile testing machine in accordance with ASTM D638 standard. Tensile strength retention rate = (tensile strength after corrosion ÷ initial tensile strength) × 100%.

[0032] The test results are shown in Table 3. Table 3 The high-energy ion treatment of Example 1 significantly improves the corrosion resistance of the material, especially in strong acid and alkaline environments.

[0033] The introduction of silicon ions in Comparative Example 4 further enhances the chemical corrosion resistance, and the performance is better than that of Example 1, especially in an acidic environment.

[0034] The ion-free treated material of Comparative Example 5 exhibits obvious corrosion weakness, especially in strong acid and salt spray environments, where the mass loss rate is high and the mechanical properties are significantly reduced.

[0035] The basic principles, main features and advantages of the present invention are shown and described above; those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only preferred examples of the present invention and are not used to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected; the scope of protection claimed by the present invention is determined by the attached claims and their effects.

Claims

1. An explosion-proof, thickened and wear-resistant rubber-plastic pipe, characterized in that: It includes an inner layer, a middle layer and an outer layer, wherein the inner layer is an ultra-high wear-resistant composite layer, which is composited with polytetrafluoroethylene and polyimide and is reinforced with nano-scale silicon carbide particles and graphene; The middle layer is an explosion-proof energy absorption layer, which uses shape memory polymers combined with cross-linked polyethylene to form an intelligent material that can respond to pressure changes, and is embedded with high-strength aramid fibers and carbon fiber composite materials; The outer layer is an explosion-proof impact barrier layer, which uses nano-ceramic reinforced silicone rubber and combines ultra-high molecular weight polyethylene with ceramic particles to improve high pressure resistance and explosion resistance; The method for preparing the explosion-proof, thickened and wear-resistant rubber-plastic pipe comprises the following steps: S1. The raw materials are fully dried before feeding, wherein the drying temperature of polytetrafluoroethylene is 120°C and the drying time is 6 hours; the drying temperature of polyimide is 160°C and the drying time is 4 hours; the drying temperature of ultra-high molecular weight polyethylene is 70°C and the drying time is 3 hours; S2. Each layer of material is preheated in sections before entering the extruder head. The first preheating temperature is 50-100°C to improve the initial flexibility of the substrate. The second preheating temperature is 100-150°C to soften the polymer material. The third preheating temperature is the melting temperature of the material + 10-20°C. The insulation time of each heating area is 1-3 minutes. S3, using a multi-head co-extrusion system, each head controls a layer of material, the barrel temperature is set to 250-320℃ for the inner layer, 220-270℃ for the middle layer, and 180-230℃ for the outer layer, and the screw speed is maintained at 60-90 rpm; S4. Through a multi-head co-extrusion mold, the molten multi-layer materials are gradually compounded, and the flow channel design in the mold is used to achieve uniform superposition of multiple layers. The mold pressure is controlled at 10-20MPa to prevent bubble generation, and then the temperature is gradually reduced through a water cooling system with a cooling rate of 1-3℃ / second.

2. The method for preparing an explosion-proof, thickened and wear-resistant rubber-plastic pipe according to claim 1, characterized in that: Polyurethane is also introduced inside the inner layer as a flexible and self-lubricating layer.

3. The method for preparing an explosion-proof, thickened and wear-resistant rubber-plastic pipe according to claim 1, characterized in that: The middle layer also incorporates a pressure-sensitive phase change material.

4. The method for preparing an explosion-proof, thickened and wear-resistant rubber-plastic pipe according to claim 1, characterized in that: The outer side of the outer layer is coated with a flame retardant coating containing fluoride.

5. The method for preparing an explosion-proof, thickened and wear-resistant rubber-plastic pipe according to claim 1, characterized in that: The explosion-proof, thickened, and wear-resistant rubber-plastic pipe interface adopts a double sealing structure, and the explosion-proof, thickened, and wear-resistant rubber-plastic pipe joint part adopts a metal+rubber composite design.

6. The method for preparing an explosion-proof, thickened and wear-resistant rubber-plastic pipe according to claim 1, characterized in that: After S4, there are the following steps: S5, coating the outer layer of the pipe with a self-repairing functional coating by spraying, and forming a thin film with self-repairing ability on the surface of the pipe by using the self-healing resin encapsulated in microcapsules.

7. The method for preparing an explosion-proof, thickened and wear-resistant rubber-plastic pipe according to claim 6, characterized in that: The shell material of the microcapsule is polyurethane, and the core is epoxy resin; the liquid epoxy resin is dispersed in the water phase by interfacial polymerization, and the capsule shell is formed by cross-linking reaction, wherein the dispersion temperature is 30-50°C, the dispersion time is 2-4 hours, the stirring speed is 2000-3000rpm, and the capsule size is controlled in the range of 10-100μm; Then, 40–60wt% polyurethane resin is selected as the base material, 20–30wt% microcapsule content is added to the solvent dimethylformamide, the coating viscosity is adjusted to 500–800cps, and it is sprayed on the outer layer of the pipe. The coating thickness is 50–200μm, the temperature is 100–120℃, and it is heated for 30–60 minutes.

8. The method for preparing an explosion-proof, thickened and wear-resistant rubber-plastic pipe according to claim 7, characterized in that: After S5, there are the following steps: S6, introducing functional ions high-energy nitrogen ions and ammonium chloride ions into the deep layer of the pipe by ion bombardment to enhance oxidation resistance, chemical corrosion resistance and adhesion strength.

9. The method for preparing an explosion-proof, thickened and wear-resistant rubber-plastic pipe according to claim 8, characterized in that: The S6 has the following steps: S6.

1. Use high-energy ion implantation equipment, equipped with two ion sources, nitrogen ion and ammonium chloride ion, to ensure that the purity of the ion source is ≥ 99.99%, and maintain the pressure in the chamber at 10 -4 –10 -6 Pa; S6.

2. Ultrasonic cleaning of the pipe using ethanol to remove surface oil, dust and other contaminants for 10–15 minutes; S6.

3. Use argon gas to clean the surface, activate the molecules on the surface of the tube, and improve the ion attachment effect. The argon gas flow rate is 20-50 standard cubic centimeters per minute, the time is 5-10 minutes, and the power is 100-200W; S6.

4. Fix the tube on a rotating sample stage to ensure that the ion beam evenly bombards every part of the tube. The sample stage rotation speed is 10–30 rpm, the injection angle is 45°–90°, the bombardment time per unit area is 10–30 seconds, and the ion penetration depth is controlled at 1–5 μm. S6.

5. After the injection is completed, the tube is annealed in a nitrogen environment to release the thermal stress generated during the ion injection process.

Citation Information

Patent Citations

  • Flame-retardant multi-layer thickened explosion-proof rubber and plastic pipe

    CN217597982U

  • Aeration steel shape memory composite film

    CN101015973A

  • Preparation method of polyethylene gas pipe material

    CN110305381A

  • Super wear-resistant and corrosion-resistant composite pipeline and preparation method thereof

    CN118836337A

Cited By

  • Multi-layer composite pipe as well as preparation method and application thereof

    CN120137241A

  • Ultrahigh-temperature insulation device of solid-waste-based high-temperature heat storage system and long-service-life operation method

    CN122091344A